Polish Security Printing Works in the system of public and economic security - Remigiusz Lewandowski (Copernican Journal of Finance & Accounting, 2013)
The article raises the issue of placing PWPW in the system of economic and public security. Two particular categories of security connected with PWPW business activity, i.e. identification and transactional security, have been defined and discussed in the article. The most essential factors affecting the above security categories as well as relations between identification/transactional security and economic/public security. The article indicates that PWPW plays an important role in the state’s economic security system and the business activity of PWPW, including banknote, document and related software’s production, creates the fundamental interest of state’s security.